Teaching EndoFLIP Impedance Planimetry to Practicing Endoscopists: An "Into the Fire" Approach to Simulation. (April 2022) - Wong, Harry J.; Su, Bailey; Attaar, Mikhail; Kuchta, Kristine; Linn, John G.; Haggerty, Stephen P.; Denham, Woody; Ujiki, Michael B.
Background. There are growing interests from practicing endoscopists to implement the functional lumen imaging probe (FLIP) impedance planimetry system. We present a simulation-based curriculum using an "into the fire" approach with hands-on pre- and post-tests to teach the use of this technology. Methods. The curriculum consists of a series of pre-tests, didactic content, mentored hands-on instructions, and post-tests. Pre- and post-testing included a knowledge-based written test, a confidence survey, and an assessment form specific to the hands-on performance of FLIP. Result. Twenty-two practicing physicians completed the curriculum. After course completion, participants had improved knowledge-based written test scores from 6.8±1.7 to 8.9±0.9 ( P <0.001), confidence scores from 10.0±5.9 to 22.1±2.6 ( P <0.001), and hands-on performance score from 11.4±3.4 to 23.1±2.0 ( P <0.001) with significant improvement in all components of the hands-on skills. Conclusion. Our simulation curriculum is effective in improving confidence, knowledge, and technical proficiency when teaching the use of FLIP to practicing physicians.